PROSES PENYIMPANAN DATA ARSIP DINAMIS MENGGUNAKAN APLIKASI SISTEM INFORMASI DIGITAL OLAH REKAM ARSIP (SIDORA) DALAM EFEKTIVITAS TEMU KEMBALI ARSIP DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN PURWAKARTA - Qowiyah, Nujma; Permana, Hinggil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the increasing volume of archives which leads to accumulation and limitations in storage space if not managed effectively. Conventional archival management is considered less efficient in supporting storage and information retrieval processes. Therefore, the implementation of a digital archival system is necessary to improve the effectiveness of records management. This study aims to analyze the process of collecting dynamic archival data using the Sistem Informasi Digital Olah Rekam Arsip (SIDORA) at the Department of Archives and Library of Purwakarta Regency, as well as its role in supporting archival management. The research employs a qualitative approach with data collection techniques including observation, interviews, and literature study. The results show that the process of collecting dynamic archival data through SIDORA is conducted systematically, starting from records receipt, identification, to data input into the system, which is equipped with information on classification, physical location, and retention period. The implementation of SIDORA has proven to enhance efficiency in storage and accelerate the retrieval process through the integration of digital data and physical archive locations. However, its implementation still faces challenges, such as dependence on technological infrastructure and the need to improve human resource competencies. Thus, SIDORA can serve as a solution for archival management in the digital era, although further development is required to optimize its utilization.